The influence of english learning platform on the improvement of cadets’ speaking skill - Sulistyorini, Dwi; Vidhiasi, Dhion Meitreya (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This research seeks to evaluate the powerfulness of the website www.englishspeak.com in enhancing the speaking skills of fourth semester cadets in Marine Mechanical Engineering Technology (TRPK) Batch 59. The research employs an experimental design featuring a pre-test and post-test format implemented for both control and experimental groups. The subjects are fourth semester cadets from the TRPK Department at Politeknik Bumi Akpelni. The sample consists of class TRPK A acting as the experimental group and class TRPK B as the control group, with both classes containing 39 cadets. The process consists of an initial meeting: a pre-test given to both groups, the second and third meetings: the experimental group undergoes treatment using www.englishspeak.com, while the control group learns via conventional methods, and the last meeting: a post-test is executed for both groups. Cadets are required to engage in basic discussions to the topic being explored. The evaluation of their speaking abilities is based on five components: pronunciation, grammar, vocabulary, content, and fluency. The results of this research indicate the average pre-test scores: experimental group: 44.20; control group: 46.46 and the average post- test scores: experimental group: 61.03; control group: 50.26. The group that was tested demonstrated progress in all five areas of speaking after using www.englishspeak.com. A t-test was performed to evaluate the significance of the outcomes. The t-value was 2.78, surpassing the t-table value of 1.67. This shows a significant difference in the post-test outcomes between the experimental group and the control group. The website www.englishspeak.com greatly enhanced the speaking skills of the cadets regarding pronunciation, sentence formation, vocabulary, substance, and speaking speed. This research shows that using interactive online learning such as www.englishspeak.com can be powerful for teaching speaking.